Case study: congestion at traffic signal of junction Jalan Bukit Ubi and Jalan Dato Lim Hoe Lek - Muhammad , Ali (2013)
Issues on the population of Malaysia keep increasing which mean the traffic demand also increasing. This may cause congestion in some traffic network. Traffic congestion will causes many negative effect to the road user and environmental. Congestion usually occurs at traffic intersection due to ineffective of traffic signal. Traffic volume analysis must be conduct to know the traffic capacity of the junction which is larger than traffic demand or not. Traffic demand is the total volume of vehicle using the road network. It can be calculate by using traffic volume survey. Then, the congestion can be classified using queue length survey to determine the delay time of the intersection. In order to propose measures as to solve both traffic congestion and traffic queuing problems that can alleviate traffic flow system at the intersection, the existing traffic congestion problem and to quantify the volume of traffic involved at the location must be investigate first.